If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -31 + 3a = 4(a + -7) Reorder the terms: -31 + 3a = 4(-7 + a) -31 + 3a = (-7 * 4 + a * 4) -31 + 3a = (-28 + 4a) Solving -31 + 3a = -28 + 4a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4a' to each side of the equation. -31 + 3a + -4a = -28 + 4a + -4a Combine like terms: 3a + -4a = -1a -31 + -1a = -28 + 4a + -4a Combine like terms: 4a + -4a = 0 -31 + -1a = -28 + 0 -31 + -1a = -28 Add '31' to each side of the equation. -31 + 31 + -1a = -28 + 31 Combine like terms: -31 + 31 = 0 0 + -1a = -28 + 31 -1a = -28 + 31 Combine like terms: -28 + 31 = 3 -1a = 3 Divide each side by '-1'. a = -3 Simplifying a = -3
| x+3(2x+5)=6 | | -8(1+3x)-6x=172 | | n-8=19-11 | | 9.21*9.21= | | n^2-12n+13=-7 | | 3(r-5)+2(r-4)=-2(r-1)+8(r+2) | | 8(7r+5)=320 | | 6x-5=109 | | 8(7r+5)=330 | | e^4x=e^2x+6 | | 2/3=2-2 | | 2a+14-13=-7 | | a^2+8a+6=-9 | | b-33=145 | | 4+2(2)+3x=11 | | 6(1-5v)=-234 | | 6-2n=-8+3(-4n-2) | | 1-3y/5-4=2y/3 | | 4(3x-5)-12(x-5)=70 | | 1+3x=4+4x | | (2x-7)y=15 | | x=x-u | | -10-9k=-91 | | -8x-3x-11=-8x+7 | | 3x-10(x+2)=sqrt(13)-7x | | -8x-3x-11=-8+7 | | 99=5n+9 | | 4(3x-5)+12(x-5)=70 | | 6-6(5+5m)=-24+8m | | X^2+5x+7=49 | | X^2+5x+58=0 | | R^3-r^2-4r+4=0 |